A 425-million-year-old Silurian pentastomid parasitic on ostracods - Siveter,DJ; Briggs,DE; Siveter,DJ; Sutton,MD (Current Biology, 2015)
Pentastomids (tongue worms) are worm-like arthropods known today from ∼140 species [1]. All but four are parasitic on vertebrates. Their life cycle typically involves larval development in an intermediate host followed by maturation in the respiratory tract of a definitive terrestrial host. Fossil pentastomids are exceedingly rare and are known only from isolated juveniles [2-6]. The identity of the possible hosts of fossil pentastomids and the origin of their lifestyle have generated much debate. A new, exceptionally preserved species, described based on adults from 425-million-year-old marine rocks, is the only known fossil pentastomid associated with a host, in this case a species of ostracod crustacean. The pentastomids are preserved near eggs within the ostracod and also, uniquely for any fossil or living pentastomid, are attached externally to the host. This discovery affirms the origin of pentastomids as ectoparasitic on marine invertebrates. The terrestrialization of pentastomids may have occurred in parallel with the vertebrate invasion of land.